The Special Legitimate Defense (The Payment of an Al Sael) in the Islamic Jurisprudence (a Study Compared to The Law) - Zeyad Hamdan Mahmood Sakhen (My University, 2008)
Aim of this Study to clarify what is meant to defend the legitimate private - pay Alsael - and the statement of what it and its legitimacy, the statement of the provisions for self- defense or offer or money, and that the damage or harm anything, and the duty of prevention and response, so that the conservation of these aspects is to preserve the necessities five God Almighty store, which not only by upright life, and to defend themselves or offering or doomed, it is not the responsibility, criminal or civil liability for performing these Alogibh; so that the performance ordered not abide provided safety. In addition to highlighting the superiority of Islamic criminal law provisions, the laws of other human condition. This came this Study in paving and four chapters of the President, where she spoke in the introductory chapter on the five necessities and prestige, and the need for preservation by the presence or scratch, and perhaps legislation provisions and perhaps criminality and punishment, and that over the legislation of the provisions is to investigate the utility, which wanted to worship God , and then talked after that discriminate on the penal system by endorsing immoral creatures, and virtue, and precedence to the maintenance of order and security and safety of the individual and society, and means to do so. I have found that the Islamic penal system; as a divine system is the best and fittest of mankind providing security and safety, and preserving the rights of privacy and symptoms and, in the prevention of crime and pieces of the eradication of corruption and spoilers. In the first quarter (what self- defense and the Special legitimacy); when speaking on the concept of self- defense within the private jurist talk, and then shown the basis and legitimacy, in terms of its nature, or that it is indeed a duty, and wisdom legitimate, and its relationship to the state of necessity, coercion, and then the comparison between him and Defense Forensic year, has shown that self-defence is the term private talk, self- defense or offer or money, which is considered old jurist under the theme Alsael payment, and that legitimacy fixed writers, Sunnis and unanimity, impact and reasonable, and that is to prevent injury and boost easily as possible, It differs from the cases of necessity and coercion in the aspects and agrees with him in other aspects; that relationship and the link between them and the legitimate defense Special close relationship is the presence of force, or threat of danger to self or event or money supply, leading to the commission of the act, which is, therefore, considered both scholars of the private and self- defense of necessity and physical coercion, applications for a (necessities permit prohibitions). In the second chapter (Departments of Defense legitimate private); showed governance legitimate self- defense or offer or money, or the same of others or offering or doomed, and scholars addressed the statements and opinions in this, and they mechanism of the evidence, then it likely stronger, and then held comparison between legitimate defense Special Sections; ranked in terms of importance or, in terms of left or waived or complacent Papaanha. I have found that self- defense or offer or money; because of the necessity and legitimacy of a social person (the maintenance and introduced his blood and preserve the rights and sanctities and property and the maintenance of honor and mind), and the conservation community is safe and provide reasons for the secretariat, and preempting the aspirants and cut out corruption and spoilers , it may leave the defense or waive any side respects, or those averse necessities of their importance; because all of the purposes for which it is to preserve Islam, and life could go only preserve and protect. In chapter III (defense Staff legitimate private and conditions); shown in this chapter of defense Staff legitimate private that must be available and presence, in order to be legitimate defence firm, owned can be used, and these elements do not have to be certain conditions should be met by the aggressor (Alsael ), or did assault (Chial) or guns (Serums it), or did the defence. This has proved to me that any disruption pillar, and the lack of quality or disruption of any provision of these conditions makes the defense already illegal, and asks the actor to do a criminal or civil responsibility. In chapter IV (a legitimate defence criminal responsibility); demonstrated the concept of criminal responsibility in the Islamic Sharia, where ancient and modern scholars, and then showed three pillars, which are essential, which is an act forbidden, and that the actor is selected, and be aware, and then showed reasons lifting criminal responsibility for the guns. This has shown me that the perpetrator would be responsible for the result of his outstanding reality punishable under criminal liability and civil liability if the three pillars, if preclude described inviolability of the act falls the responsibility. This causes the lifting criminal responsibility for the actor are: self-defence year, and defending the legitimate private, and acts of the rulers, duties, and telemedicine, discipline and Equestrian Games, and the rhythm of the Mahdrin punishment, or the reasons for its failure are: coercion and sugar sittings, and insanity, and the small people. This researcher has found that guns also responsible if the project exceeded the increase in its defense of the sum required intentionally, deliberately If damage Balsael over the extent necessary to stop the aggression was not gradual, it will be responsible for this waiver, both criminal and civil. If beyond that of a mistake-induced, questioned about his criminal responsibility not intentional.

تهدف هذه الرسالة إلى توضيح المقصود بالدفاع الشرعي الخاص دفع الصائل- وبيان ماهيته ومشروعيته، وبيان أحكام الدفاع عن النفس أو العرض أو المال، وأن الإضرار أو إلحاق الأذى بأي شيء من ذلك، واجب منعه ورده، ذلك أن الحفاظ على هذه الجوانب هو حفاظ على الضرورات الخمس التي أمر الله تعالى بحفظها، والتي لا تستقيم الحياة إلا بها، وأن المدافع عن نفسه أو عرضه أو ماله، لا مسؤولية عليه، مسؤولية جنائية أو مدنية، لقيامه بهذه الوجيبة؛ ذلك أن أداء المأمور به لا يتقيد بشرط السلامة. هذا فضلاً عن إبراز التفوق لأحكام القانون الجنائي الإسلامي، على غيره من القوانين البشرية الوضعية. هذا وقد جاءت رسالتي هذه في تمهيد وأربعة فصول رئيسة، حيث تحدثت في الفصل التمهيدي عن الضرورات الخمس ومكانتها، وضرورة حفظها من جانب الوجود أو العدم، وعن علة تشريع الأحكام وعلة التجريم والعقاب، وأن مدار التشريع للأحكام هو تحري المصلحة، التي أرادها الله تعالى لعباده، ثم تحدثت بعد ذلك عن تميز النظام الجنائي بإقراره للآداب والخلق والفضيلة، وعن أسبقيته في حفظ النظام والأمن والأمان للفرد والمجتمع، ووسائله في ذلك. وقد تبيّن لي أن النظام الجنائي الإسلامي؛ كونه نظاماً ربانياً هو النظام الأفضل والأصلح للبشرية بتوفير الأمن والأمان، وحفاظه على الحقوق والأعراض والحرمات، وفي منعه للجريمة وقطعه لشأفة الفساد والمفسدين. وفي الفصل الأول (ماهية الدفاع الشرعي الخاص ومدى مشروعيته)؛ تحدثت فيه عن مفهوم الدفاع الشرعي الخاص بالمعنى الفقهي الحديث، ثم بيّنت أساسه ومشروعيته، وطبيعته من حيث كونه حقا أم واجبا، وحكمه الشرعي، وعلاقته بحالة الضرورة والإكراه، ثم عقدت مقارنة بينه وبين الدفاع الشرعي العام، وقد بينت أن الدفاع الشرعي الخاص هو المصطلح الحديث، للدفاع عن النفس أو العرض أو المال، وهو ما بحثه الفقهاء قديماً تحت موضوع دفع الصائل، وأن مشروعيته ثابتة بالكتاب والسنة والإجماع والأثر والمعقول، وأنه قائم على منع الضرر ودفعه بأيسر ما يمكن، وأنه يختلف عن حالتي الضرورة والإكراه في جوانب ويتفق معه في جوانب أخرى؛ ذلك أن العلاقة والصلة بينهما وبين الدفاع الشرعي الخاص علاقة وثيقة وهي وجود الاضطرار، أو التهديد بخطر حالّ على النفس أو العرض أو المال، تؤدي إلى ارتكاب الفعل المحرم، ولذلك اعتبر الفقهاء كلاً من الدفاع الشرعي الخاص والضرورة والإكراه المادي ، تطبيقات لقاعدة (الضرورات تبيح المحظورات). وفي الفصل الثاني (أقسام الدفاع الشرعي الخاص)؛ بينت الحكم الشرعي للدفاع عن النفس أو العرض أو المال، أو نفس الغير أو عرضه أو ماله، وتناولت أقوال الفقهاء وآراءهم في ذلك، وما استندوا إليه من أدلة، ثم رجحت الأقوى منها، ثم عقدت مقارنة بين أقسام الدفاع الشرعي الخاص؛ من حيث ترتيبها وأهميتها أو من حيث تركها أو التنازل عنها أو الرضى بإباحتها. وقد تبيّن لي وجوب الدفاع عن النفس أو العرض أو المال؛ لما في ذلك من ضرورة شرعية واجتماعية للفرد (بصون عرضه ودمه وبالحفاظ على حقوقه وحرماته وأملاكه وصون شرفه واعتباره)، وللمجتمع المسلم بحفظ أمنه وتوفير أسباب أمانه، وقطع الطريق أمام الطامعين وقطع شأفة الفساد والمفسدين، فلا يجوز ترك الدفاع أو التنازل عن أي جنب من جوانبه، أو إباحة تلك الضرورات لأهميتها؛ لأنها جميعها من المقاصد التي أمر الإسلام بالحفاظ عليها، ولا تستقيم الحياة إلا بصونها وحمايتها. وفي الفصل الثالث (أركان الدفاع الشرعي الخاص وشروطه)؛ بيّنت في هذا الفصل أركان الدفاع الشرعي الخاص التي لا بد من توافرها ووجودها، حتى يكون الدفاع مشروعاً ثابتاً لصاحبه يمكن له استخدامه، وهذه الأركان لا بد لها من شروط معينة ينبغي توافرها في المعتدي (الصائل) أو فعل الاعتداء (الصيال) أو المدافع (المصول عليه) أو فعل الدفاع. هذا وقد تبين لي أن اختلال أي ركن من هذه الأركان، وعدم وجوده أو اختلال أي شرط من هذه الشروط يجعل الدفاع فعلاً غير مشروع، ويُسأل الفاعل عن فعله مسؤولية جنائية أو مدنية. وفي الفصل الرابع (علاقة الدفاع الشرعي بالمسؤولية الجنائية)؛ بيّنت مفهوم المسؤولية الجنائية في الشريعة الإسلامية، عند الفقهاء القدماء والمحدثين، ثم بينت أركانها الثلاثة التي لا بد منها، وهي إتيان فعل محرم، وأن يكون الفاعل مختاراً، وأن يكون مدركاً، ثم بيّنت أسباب رفع المسؤولية الجنائية على المدافع. هذا وقد تبين لي أن الجاني يكون مسؤولاً عن نتيجة فعله مستحقاً للعقاب واقعاً تحت طائلة المساءلة الجنائية والمدنية إذا توفرت للمسؤولية أركانها الثلاثة، فإذا انتفت صفة الحرمة عن الفعل تسقط المسؤولية. هذا وأسباب رفع المسؤولية الجنائية عن الفاعل هي: الدفاع الشرعي العام، والدفاع الشرعي الخاص، وأعمال الحكام وواجباتهم، والتطبيب، والتأديب، وألعاب الفروسية، وإيقاع العقاب على المهدرين، وأما أسباب امتناعها فهي: الإكراه والسكر بعذر، والجنون، وصغر السن. هذا وقد تبين للباحث أيضاً أن المدافع مسؤول إذا تجاوز في دفاعه المشروع بالزيادة على القدر المطلوب عمداً، فإذا تعمد الإضرار بالصائل بما يزيد عن الحد اللازم لوقفه عن العدوان ولم يكن متدرجاً، فإنه يكون مسؤولاً عن هذا التجاوز من الناحيتين الجنائية والمدنية. أما إذا تجاوز ذلك من باب الخطأ غير العمدي، فيُسأل عن فعله مسؤولية جنائية غير عمدية.
(الدفاع الشرعي الخاص (دفع الصائل) في الفقه الإسلامي (دراسة مقارنة مع القانون الوضعي